Karakterisasi morfologi, kromosom,Dan profil protein plasma darah Untuk penentuan jenis kelamin burung Gelatik (Padda oryzivora (L.)=The Characterization of Morphological, Chromosomes, and Protein Profile of Blood Plasma - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
The Java sparrow is monomorphic, which was difficult to determine their sex morphologically. The use of morphological characteristics for determination of Java sparrow sex has been doubt. Therefore, the observation of chromosomes and certain protein profile of blood plasma were conducted in order to support for determination of sex. The investigation was communed by selection of morphological characteristics related to methods of Petinggil, King and Dickinson. The results of morphological characterization, such as body size, red color bill, the meeting of the bill point, and length of barbulae may be used for identifying the sex of the Java sparrow. Observation of chromosomes was conducted by preparing chromosomes from bone marrow leucocyte of Java sparrow femur, using Tjio and Whang method. Chromosomes type was analyzed using centromer index. Based on chromosome pairs, an acrocentrictype Z chromosomes and submetacentric-type W chromosome were found in the female Java sparrow, while sex chromosome pairs in the male Java sparrow was difficult to identity. The blood plasma protein was visualized through the gel electrophoresis with sodium dodecyl sulphate (SDS). Gel electrophorezed demonstrated protein profile of blood plasma in the form of bands. Most of Java sparrow possessed varies of protein bands, consisted of a very thick band identified as albumin (66 Kda) and 3 to 5 thinner bands underneath. This protein profile particularly for the male Java sparrow from different area. The appearance of the female Java sparrow protein on gel was similar but simpler than the one of the male. The results of chromosomes and protein an gel are very useful for sex determination.